OP0215 THE RISK OF FIRST AND SUBSEQUENT FRACTURES IN PATIENTS WITH RHEUMATOID ARTHRITIS IN THE UK. (June 2019) - Erwin, Jo; Enki, Doyo; Woolf, Anthony
Abstract : Background: Osteoporosis is a well-known complication of rheumatoid arthritis (RA) (1). NICE advises that health providers do not routinely assess fracture risk in people with RA aged under 50 years unless they have other major risk factors. However, studies suggest that young people with RA are at increased fracture risk even before age 50 years (2-4). Objectives: To measure the incidence and risk of first and subsequent fracture in adults with RA aged under 50 in the UK. Methods: A retrospective observational cohort study with matched control using data from Clinical Practice Research Datalink (CPRD) of adults ≥18 years with diagnosis of RA recorded from 1987 to 2016. Patients were followed from index date to the first fracture and subsequent fracture. Cases were adults with a new diagnosis of RA with at least one day of follow-up during the period. These cases were matched to 3 controls by age, sex, GP surgery and calendar year. The date of RA diagnosis date is the index date for cases and their matched controls. CPRD data has a high level of data validity in reporting of fractures but subsequent fractures may be recorded more than once. In this analysis when subsequent fractures were of the same body part the fracture had to occur at least 6 months after the previous fracture to be classified as a "subsequent fracture". "First fracture" is the first fracture occurring after the index. "Subsequent fracture" is the fracture occurring after the first fracture. "Pre-index fracture" is a fracture that occurs before the index date. Results: The characteristics of the study population are shown in Table 1. The incidence rate of first fracture for cases was 9.02 per 1000-person years (95% CI 8.46-9.61), for controls 6.85 per 1000-person years (95% CI 6.55-7.15). The incidence rate ratio (IRR) for first fracture was 1.32 (95% CI 1.220-1.426; p=0.00). The incidence rate of subsequent fracture was 1.78 (95% CI 1.55-2.05) per 1000-person years for cases and 1.17 (1.05-1.29) per 1000 -person years for controls. The IRR for subsequent fracture was 1.53 (95% CI 1.283-1.833; p=0.00). A Cox's proportional hazards model was used to estimate the hazard (or risk) of first and subsequent fracture for cases and controls stratified by age. Those with a pre-index fracture and with a glucocorticoid prescription prior to the index date had significantly higher hazard ratios for first and subsequent fracture. Women had a higher hazard ratio for first fracture. Conclusion: This study shows that the incidence of fracture in patients with RA aged under 50 is significantly higher than in matched controls. This is true for the first fracture and for the subsequent fracture and is significantly higher for women in those under 50 for first fractures. References: [1] Van Staa TP, Geusens P, Bijlsma JWJ, et al. Clinical assessment of the longterm risk of fracture in patients with rheumatoid arthritis. Arthritis & Rheumatism. 2006; 54(10): 3104–3112. [2] Amin S, Gabriel SE, Achenbach SJ, et al. Are Young Women and Men with Rheumatoid Arthritis at Risk for Fragility Fractures? A Population-Based Study. J Rheumatol. 2013; 40(10): 1669–1676. [3] Kim SY, Schneeweiss S, Liu J, et al. Risk of osteoporotic fracture in a large population-based cohort of patients with rheumatoid arthritis. Arthritis Research & Therapy. 2010; 12(4):R154. [4] El Maghraoui A, Rezqi A, Mounach A, et al. Prevalence and risk factors of vertebral fractures in women with rheumatoid arthritis using vertebral fracture assessment. Rheumatology. 2010; 49(7):1303–1310. Disclosure of Interests: Jo Erwin Grant/research support from: Pfizer, Doyo Enki Grant/research support from: Pfizer, Anthony Woolf Grant/research support from: Pfizer